Economic Empowerment of Pesantren Through Agribusiness (Study On Al-Mawaddah Entrepreneurial Pesantren) - Muhammad Baqi Mustaghfiri (Journal of Islamic Economic Laws, 2020)
This paper aims for several research objectives. It aims to find out the agribusiness sectors developed by Al-Mawaddah Entrepreneurial Pesantren. It also aims to find out the empowerment of agribusiness developed by this pesantren. Last, it also aims to determine the impact of empowering agribusiness developed on improving the economy Al-Mawaddah Entrepreneurial Pesantren’s alumni. This research is a field research. The approach used by researcher is a qualitative descriptive approach with a case study strategy. Research location is at Pesantren Entrepreneur AlMawaddah Honggosoco Kudus RT. 06/ RW. 01, Jekulo District, Kudus Regency. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is descriptive qualitative. The results show that: (1) the agribusiness sector that was developed at Al-Mawaddah Entrepreneurial Pesantren touched only agriculture and educational sectors; (2) Agribusiness Empowerment developed by Al-Mawaddah Entrepreneurial Pesantren consists of three stages, namely: input, process, and output; (3) Agribusiness entrepreneurship is better than working under other people.